CFA in SEM by LISREL-Assisted to Test The Construct Validity of The Performance of The Sanrobone Elementary School Principal in South Sulawesi Province - Rafiuddin, Rafiuddin; Irham, Irham; Nurjihadin, Nurjihadin; Syarifuddin, Syarifuddin; Rahmat, Farah Alfian Ghofar (MSJ : Majority Science Journal, 2025)
This study aims to test the validity of the construct of the performance of elementary school principals in South Sulawesi Province using CFA in SEM on ​​the LISREL application based on the components of leadership, management, and personality. This type of research is ex-post facto. The number of samples collected through stratified purposive random sampling was 100 respondents with details of 15 principals, 75 class teachers, 5 religious-teachers, and 5 sports teachers in elementary schools in Sanrobone. The data collection technique used a principal performance questionnaire with 4 indicators of leadership, 4 indicators of management, and 7 indicators of personality, as well as documentation of the principal's performance. The research data were analyzed using descriptive statistical from CFA data. The results showed that the construct validity tested using CFA on the principal's performance in the leadership, management, and personality components showed goodness of fit based on the results of the goodness of fit index with the measurement model on the Absolute/Predictive fit Index criteria, namely on RMSEA 0.0057 from the limit value ≤ 0.08; RMR 0.069 from the limit value ≤ 0.1, on the Comparative Index criteria, namely on IFI and CFI each 0.92 from the limit value> 0.90, although on the Parsimony fit Index criteria, namely PNFI and PGFI each below the limit value> 0.90 but not significant. The conclusion of each indicator item contribution also shows that it is greater than the selected standardized solution value, which is greater than 0.3, so it is strong enough to explain the latent variable (principal performance).